Effectiveness of Different Binders in Improving Feed Stability and Survival Rate of Mud Crab (Scylla sp.) Fed Trash Fish-Based Diet - Diamahesa, Wastu Ayu; Abidin, Zaenal; Lestari, Dewi Putri; Alim, Sahrul; Rahmadani, Thoy Batun Citra; Mutiara, Ni Luh (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Feed stability is crucial in aquaculture to minimize nutrient loss and ensure optimal growth of cultured species. This study evaluated the effects of different binders (carboxymethyl cellulose/CMC, wheat gluten, tapioca flour, and Gracilaria sp. flour) at 3% and 5% concentrations, processed via hot and cold mixing methods, on feed stability and survival of mud crab (Scylla spp.). Conducted over 45 days, the research involved feed formulation, stability testing in seawater (30 ppt salinity), and a 30-day feeding trial in a recirculating aquaculture system. Results showed that binder type and processing method significantly influenced feed integrity, with CMC 5% + hot mixing exhibiting the highest stability (96.99% retention after 240 minutes), while tapioca 5% + hot mixing degraded fastest. All formulations met the ≥70% stability threshold after 120 minutes, confirming suitability for aquaculture. The feeding trial revealed 100% survival across all treatments, indicating that binder selection can prioritize physical stability without compromising crab health. Hot processing consistently enhanced binder performance, particularly for polysaccharide-based CMC and Gracilaria sp. flour. These findings suggest CMC 5% (hot) as the optimal binder for durable mud crab feed, whereas tapioca requires careful concentration control. The study provides practical insights for feed development, though further replicated trials under varied farming conditions are recommended to validate commercial applicability. This research contributes to sustainable aquaculture by improving feed efficiency and reducing waste in mud crab production.